(untitled) (The International Journal for Scientific Research, 2026)
The study aims to analyze the variables of the digital economy on attracting foreign direct investment through several economic and digital variables (per capita GDP, total Internet users as a percentage of the population, broadband subscriptions, capital formation as a percentage of GDP) for the period 1998-2024 Singapore as a model, taking into account the time impact of foreign investment The study relied on time series testing using the extended Dickey-Fuller test (ADF), and it was found that it became stable after taking the first time difference, which necessitated the use of the AR1 autoregression model, including the lag variable To explain the relationship between variables and to address the problem of autocorrelation. The results showed that the model explains 75.3% of the change in foreign investment, and that all variables have statistical significance at a significance level of 5% the value of Adjusted R was 0.681, which indicates the explanatory power of the model. The study concluded the importance of enhancing digital infrastructure and the total per capita GDP, as it plays an effective role in attracting foreign direct investment.